Features of Cirrhotic Cardiomyopathy Early in the Lives of Infants With Biliary Atresia Correlate With Outcomes Following Kasai Portoenterostomy. Issue 6 (21st January 2022) - Morrison, Jhavene; Ferguson, Eric; Figueroa, Janet; Karpen, Saul J.
Abstract : Cirrhotic cardiomyopathy (CCM), detected during two‐dimensional echocardiography (2DE), is prevalent in patients with biliary atresia (BA) awaiting transplant. Whether CCM occurs early in the lives of infants with BA is unknown. The aim of this study was to explore the incidence and consequence of CCM in patients with BA, focusing on the earliest ages when 2DE was performed. A cohort of 78 patients with BA at a single center underwent 2DE (median age = 132 days) during the first year of life. Left ventricular mass index (LVMI) to upper limit of normal (ULN) ratio ≥ 1.0 was present in 60% of patients who never underwent Kasai portoenterostomy (KPE; n = 15), 49% with nondraining KPE (n = 41), and 21% with draining KPE (n = 19). Patients with a draining KPE (median age at 2DE = 72 days) had a lower LVMI/ULN ratio (0.75 [interquartile range [IQR] 0.70, 0.91]) compared to those with a nondraining KPE (0.99 [IQR 0.78, 1.17] median age of 141 days; P = 0.012). In those whose 2DE was performed within 7 days of KPE (n = 19, median age of 61 days), the LVMI/ULN ratio was lower in those with a future draining KPE (0.73 [IQR 0.66, 0.75]) compared to the group with a future nondraining KPE (1.03 [IQR 0.88, 1.08], P = 0.002). Logistic regression modeling revealed LVMI/ULN ratio ≥ 1.0 as a predictor of KPE outcome, with an odds ratio of 16.7 (95% confidence interval 1.36‐204; P = 0.028) for a future nondraining KPE compared to those with a LVMI/ULN ratio < 1.0. Conclusion: 2DE early in the lives of patients with BA revealed features of CCM that correlated with future outcomes. If validated in a multicenter study, this could lead to 2DE as a useful clinical tool in the care of infants with BA.